Caregiving for Persons With Dementia: Evidence-Based Resources for SLPs. Issue 1 (January 2019) - Bourgeois, Michelle S.
Abstract : Speech–language pathologists (SLPs) have an important role in supporting the caregivers of persons with dementia from diagnosis through the end of life in 4 major areas: education, training to use effective cognitive communication strategies identified for clients with dementia, psychosocial/emotional support, and counseling. Speech–language pathologists may be involved in this process from the initial diagnosis when families need guidance to navigate the vast amounts of information on the Internet and elsewhere, until they need assistance in making end-of-life decisions. Speech–language pathologists must recognize that caregivers have needs, and differing needs, depending on the stage of dementia of the person to whom they are providing care. The research in caregiving interventions for family, professional, and paraprofessional caregivers provides an understanding of effective, evidence-based approaches, resources, and promising caregiver outcomes for the SLP working with individuals with dementia and their caregivers. It is important for SLPs to know that these interventions exist and to seek out appropriate services to which to refer the caregivers of their clients. Other person-centered interventions specifically developed for SLPs to implement with their clients with dementia and their family and professional caregivers are crucial for ensuring a quality life for clients and caregivers and for meeting the demands of a quality dementia care workforce.